Formula Tepung Petul untuk Memperbaiki Status Gizi dan Kolesterol Total pada Wanita Menopause Hiperkolesterolemia - Sufiati Bintanah; Mufnaetty Mufnaetty (Universitas Muhammadiyah Semarang, 2021)
A decrease in the hormone estrogen in women can trigger changes in nutritional status and cholesterol levels that cause hypercholesterolemia, so that antioxidant compounds and fiber are needed to improve one of them is in tempeh flour and rice bran. This study aims to prove the effect ofgiving a combination of tempeh flour and bran (Petul) on nutritional status and total cholesterol levels in menopausal women with hypercholesterolemia. Methods: Randomized control group pretest posttestcontrol group design, carried out on 60 menopausal women at least 1 year with hypercholesterolemia, not taking medication who were divided into intervention groups (given a formula 37.33 g / drink 3 times a day for 3 weeks) and placebo in the control group. The variables studied before and after the intervention were nutritional status and total cholesterol levels.Independent statistical analysis of t test, dependent t test and Ring spearmen correlation test. Results: Combination of PETUL as much as 37.33 g / drink 3 times / day for 3 weeks can improve nutritional status but has no significant and significant effect on reducing total cholesterol levels. Consclusion : PETUL formula can improve nutritional status and reduce total cholesterol levels.Keywords: Formula, Petul, nutritional status, menopausal women, hypercholesterolemia